2002
DOI: 10.1007/s00464-001-9183-6
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of intraoperative cholangiography to incidence and outcome of common bile duct injuries during laparoscopic cholecystectomy

Abstract: The use of IOC can avoid severe types of CBD injuries during LC, increase the recognition at the time operation, and influence the success of repair and outcome of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
115
1
8

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 2 publications
5
115
1
8
Order By: Relevance
“…Archer et al [13] reported that routine use of IOC increased detection of BDI from 45 % to 85 %, which is similar to the increased detection described by Ludwig et al [9] from 45 % to 90 %. Intraoperative detection of a ductal injury should decrease the technical difficulty of a repair, because there is no infection, inflammation, or fibrosis in the operating field compared with a delayed repair.…”
Section: Importance Of Intraoperative Detection Of Bdisupporting
confidence: 67%
See 3 more Smart Citations
“…Archer et al [13] reported that routine use of IOC increased detection of BDI from 45 % to 85 %, which is similar to the increased detection described by Ludwig et al [9] from 45 % to 90 %. Intraoperative detection of a ductal injury should decrease the technical difficulty of a repair, because there is no infection, inflammation, or fibrosis in the operating field compared with a delayed repair.…”
Section: Importance Of Intraoperative Detection Of Bdisupporting
confidence: 67%
“…Performing IOC means an increased operative time, which has been reported in the literature as 8, 10, 16, and 20 min respectively [9,58,67,68]. However, studies have indicated that despite the increased time in operative procedure and materials, routine IOC is cost-effective by reducing the severity of bile duct injury and the cost of treatment of patients with retained stones who did not receive IOC [56,61,69].…”
Section: Role Of Intraoperative Cholangiogram (Ioc): a Literature Ovementioning
confidence: 99%
See 2 more Smart Citations
“…A metaanalysis of 40 case series detailing 327,523 LCs and 405 major injuries was performed in 2002. 23 Rate of injury was halved in the routine IOC group (0.21%) as compared with the selective group (0.43%). In addition, in the selective group, only 21.7% of CBD injuries were detected intraoperatively.…”
Section: 21mentioning
confidence: 86%